Effect of Addition of Seaweed Flour (Eucheuma Cottoni) And Soy Bean Flour (Glycine Max) On Tapioca Noodles - Tengku Mia Rahmiati; Zulfikar Zulfikar; Salfauqi Nurman (Serambi Journal of Agricultural Technology, 2019)
Tapioca dried noodles are one of the results of food diversification. To increase the nutritional value of tapioca dried noodles, the addition of soybean flour and seaweed flour is done. This study was aimed at finding out the effect of seaweed flour and soybean flour additions on the physicochemical characteristics of dried noodles. The research was conducted using completely randomized design (CRD) factorial focussing on 2 factors, the addition of seaweed flour (L) (35, 25 and 15 grams) and the addition of soybean flour (K) (15, 25 and 35 grams). The observations consisted of organoleptic tests, water absorption test analysis, water content analysis and protein content analysis. The results of this study indicated that the best formulation of dried noodles was the analysis result (L1K2) with organoleptic results on color 4.34 (like), flavor 4.43 (like), taste 4.46 (like) and texture 4.21 (like). In addition, the physical chemical characteristics was the value of water absorption (394.16%), water content (9.6%) and protein content (13.12%).